1999
DOI: 10.1007/s004360050609
|View full text |Cite
|
Sign up to set email alerts
|

Calomys callosus (Rodentia: Cricetidae) trophoblast cells as host cells to Toxoplasma gondii in early pregnancy

Abstract: The potential of the RH strain of Toxoplasma gondii to invade trophoblast cells of the cricetid rodent Calomys callosus in a congenital infection in the initial third of pregnancy was investigated in this study using morphological and immunocytochemical approaches. The animals were intraperitoneally inoculated on the 1st day of pregnancy and the infection was observed on day 7. Various numbers of parasites could be observed inside the parasitophorous vacuoles in trophoblastic cells under light and electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…52 Intravillous cytotrophoblasts produce MIF in response to T. gondii soluble extract; and then, ICAM-1 is induced in the syncytiotrophoblast maternal face. [53][54][55] Hypothetically, the maternal À179T low-expression allele of IFN-g, as well as the fetal Kilifi allele of ICAM-1 or the low-expression haplotype of MIF, would be compatible with resistance against vertical transmission (Table 1). 43,[56][57][58] TNF-a is a key cytokine in acquired toxoplasmosis control.…”
Section: Immune Response In Acquired Toxoplasmosismentioning
confidence: 99%
“…52 Intravillous cytotrophoblasts produce MIF in response to T. gondii soluble extract; and then, ICAM-1 is induced in the syncytiotrophoblast maternal face. [53][54][55] Hypothetically, the maternal À179T low-expression allele of IFN-g, as well as the fetal Kilifi allele of ICAM-1 or the low-expression haplotype of MIF, would be compatible with resistance against vertical transmission (Table 1). 43,[56][57][58] TNF-a is a key cytokine in acquired toxoplasmosis control.…”
Section: Immune Response In Acquired Toxoplasmosismentioning
confidence: 99%
“…Previous studies have shown that C. callosus is highly susceptible to T. gondii, suggesting an alternative model for the study of experimental toxoplasmosis (FavoretoJunior et al 1998;Ferro et al 1999;Pereira et al 1999).…”
Section: Introductionmentioning
confidence: 98%
“…C. callosus, a wild mouse-like autochthonous rodent from South America, is a reservoir for various infectious agents [13]. This animal is highly susceptible to T. gondii infection, and it has been used as an appropriate alternative model to study experimental toxoplasmosis [12,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%